African Countries and the Green Box - Oduro, A.D. (Cambridge University Press, Cambridge, 2009)
The paper argues that the green box subsidies of the WTO’s Agreement on Agriculture provide African countries the policy space to implement measures to support agriculture. Evidence from African countries that notify the WTO of their domestic support to agriculture suggests that a large proportion of this support falls under the green box. In addition not all the available green box measures are used by African countries or may be considered priorities at this point in time. The categories of spending that may be considered priorities to African agriculture are all available under the green box measures with limited restrictions on their use. The effective use of spending on green box measures will go a long way to reduce the constraints facing African farmers.
Keywords: Agriculture subsidies; WTO